PENGARUH LATIHAN PLYOMETRICS TERHADAP PENINGKATAN KETERAMPILAN LAY-UP BOLABASKET - Achmad Nuryadi (LPPM Universitas PGRI Adi Buana Surabaya, 2016)
The mastery of various techniques and good basic right, allowing players to show a good game anyway. In accordance with the opinion of M. Sajoto that a use and application of good engineering and in the right moment, will be a tactical game that does not need to be trained separately. Kosasih shooting is basic basketball skills of the best known and most popular. Wissel reveals that the ability to be controlled by a player is the ability to put the ball or shoting. This is consistent with the objective of a basketball game that requires for each team to memsukkan ball as much as possible to the opponent's basket or basket and prevent the opposing party do similar things. Lay-up was an attempt to enter the ball into the basketball hoop or basket with two steps and jumped in order to gain points. Lay-up is also called the shot floated and the possibility ball into the lay-up is immense. Plyometrics exercise is one exercise that is done to generate explosive power capability leg muscles or arm muscles. The goal of this research is to analyze the application of plyometrics exercises to achievement lay-up in basketball with the design of the study is Preexperimental design by using one group pretest-posttest design. Key word: Plyometrics workout and lay-up results